Investigating EFL Students’ Environment Analysis on English Speaking Competencies at Senior High School - Harahap, Prisca Apriana; Khairunisa, Hanifah; Ananda, Shifa; Apoko, Tri Wintolo (English Education:Journal of English Teaching and Research, 2024)
English speaking is one skill or competence of English that should be owned by EFL students in the era of 21stcentury. Thus, each EFL student needs to achieve the abilities of oral communication in English better. However, teachers of English often neglect the students’ constraints in learning English. Not many studies are discussing about environment analysis on English speaking competencies. This study aims to analyze EFL students’ environment on English speaking in senior high schools. This current study employed a qualitative design to capture the students’ responses on learning environments. The participants of this study were four students of senior high school level in state and private schools in Jakarta and Depok, West Java, Indonesia. The results showed that EFL students’ interest, motivation, time, and their classroom significantly could impact their English-speaking ability. Thus, this study recommends that teachers of English should motivate the students to learn English better and accommodate them with comfortable classroom.